PROTO MALAYIC VOWEL PHONEME REFLEX IN MALAY LANGUAGE - Nadra Nadra; Rina Marnita; Muhammad Alfikri; Atri Kehana Masni (Sosiohumaniora, 2022)
The Malay language is spoken in a relatively wide area in Indonesia. One of the areas is the Merangin Regency, Jambi province. Prior studies indicate that the Malay language in Merangin has not yet received much attention, especially one that examines its relationship with the parent language. This study aims to explicate the Proto Malayic vowel phoneme reflexes in the Malay language spoken in the regency. Data for this field research is obtained from participants, in 4 observation points, who have responded to a list of structured questions and from the speakers whose conversing is recorded. The comparative method is used to analyze the data and the top-down approach is employed to see the reflexes. This study found that the Proto-Malayic vowel phoneme reflexes in the Observation Point 1 has more variations than those in other points. The variations which are determined by the environment or places in which the vowel phoneme exists generally occur in the ultimate syllable. The variations are very likely caused by the influence of other languages, including the languages of the immigrants living in the observed area.